Improving an analytical gyroscope azimuth mode to compensate for the ballistic deviation of a marine gyrocompass - Ivanov, Sergiy; Oliinyk, Pavlo; Virchenko, Gennadii (Eastern-European Journal of Enterprise Technologies, 2022)
One of the main errors of the gyrocompass is ballistic deviance, which occurs when maneuvering a vessel. This is an important aspect related to solving the issue of navigational safety, which is the object of this research. As part of the study, it is proposed to improve the regime of analytical gyroscope azimuth to compensate for the ballistic deviance of marine gyrocompass, which is the subject of current scientific research. When using the classic technique for reducing ballistic deviance (physical switching of the device to the mode of gyroscope azimuth), under certain conditions the gyrocompass after the maneuver may not return to the meridian and lose its performance. At the same time, classical algorithmic compensation by calculating ballistic deviance requires information from external devices, such as a lag and/or a GPS receiver (Global Positioning System). To compensate for ballistic deviance, this work has improved the mode of analytical gyroscope azimuth, designed to enhance the accuracy of the marine gyrocompass on the maneuver, by using a third-order filter accelerometer for filtration. This makes it possible to compensate for ballistic deviance and reduce intercardinal deviance during pitching. The current paper proposes a procedure for calculating the switching time between gyrocompass modes, which makes it possible to obtain the predefined value of ballistic deviance. As a result, the improved technique to reduce deviance demonstrates an accuracy comparable to the classical one. When using this technique, the loss by gyrocompass of the properties of selectivity relative to the meridian (indication of the course) is excluded because the device does not switch to a gyroscope azimuth mode. The proposed observation device can be used on standard gyrocompasses without the need for reconfiguration and achieve the desired value of the residual error of deviance compensation (according to calculations, up to 0.3°)